الإبداع الإداري لدى مدراء رياض الأطفال في محافظة دهوك وعلاقته ببعض المتغيرات - عبدالله, بشكوش جعفر (Sulaimani Journal for Humanities, 2021)
This study aims to investigate about the level of administrative creativity of the headmasters of kindergartens in relation with some variables like the duration of administrative work and kind and location of the kindergarten. The researcher used the quantitative descriptive method in this study and used questionnaire to collect data that consisted of (20) items distributed on (4) axes which are (fluency, originality, flexibility and sensitivity to problems). The sample of the study consists of (68) headmasters from both sexes. One and independent sample T. Test was used in addition to one way annova, weighted mean, Alpha Cronbach. The result showed that the headmasters run their institutions in a creative way and the variables of the study are not significant, they also showed that originality came in the first place then the sensitivity to problems followed by flexibility and in the last position came flouncy.